Pengalaman Karyawan: Cara Menarik Bakat, Mempertahankan Karyawan, Berkinerja Terbaik, Dan Mendorong Hasil - Yessica Pauline Riani Purba; Abdul Basith Mirahardikusuma; Akhdan Assad Al Hakim; Linda Purnamasari; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2023)
Purpose - This research aims to test how much motivation, rewards, professional or personal closeness, training, education, facilities and infrastructure contribute to improving employee performance. Findings - The results of the literature review show that discipline can improve employee performance indirectly through motivation. Design/methodology/approach-This research uses a structural equation modeling model which shows that motivation, reward, professional or personal closeness, training, education, facilities and infrastructure have a positive and significant influence on employee performance. Originality/value-This research shows an innovative view that companies need to retain top performing employees by using experience, good talent management, and motivation. By focusing on the best results from employees, this article provides insight into the importance of companies carrying out good talent management for their employees to drive results for the company. The value of this article is that it provides practical guidance for companies who want to find the best talent for the company to encourage the best performing employees who produce good results for companies who want to improve employee performance and encourage maximum results for the company.